Meningkatkan Kinerja Perusahaan Asuransi : Strategi Pengelolaan Sumber Daya Manusia dalam Mencapai Tujuan Perusahaan - Muhammad Bima Nugraha; Zainarti Zainarti (Jurnal Manajemen dan Ekonomi Kreatif, 2025)
This article aims to analyze human resource (HR) management strategies in enhancing the performance of insurance companies and how effective HR management contributes to achieving corporate goals. The research utilizes a qualitative approach, collecting data through in-depth interviews and document analysis related to HR management in insurance companies. The findings show that effective HR management practices, such as employee training, proper performance evaluations, and motivation through reward systems, play a crucial role in improving the performance of insurance companies. Additionally, adaptation to technology and change management were found to be key factors in achieving more efficient and sustainable corporate objectives.